Meningkatkan Hasil Belajar Matematika Melalui Media Papan Puzzle Pecahan Pada Siswa Sekolah Dasar - izzatul jannah; Agung Setyawan (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
This study aims to determine the improvement of student learning outcomes using fractional puzzle board media. Based on the results of observations made by researchers at SDN Bancaran 3 Bangkalan, there are problems, namely the media used in learning is still limited, namely using simple theme books and companion books. The method used by the author in this research is the Classroom Action Research (CAR) method and uses the Kemmis and Mc. Taggar method which is carried out in two cycles. Each cycle has four stages, namely planning, action, observation, and reflection. The research site is at SDN Bancaran 3 Bangkalan , with the research subject of class II B students as many as 8 students. The data collection techniques used were tests, observations, and documentation. This study used an instrument in the form of test questions. Based on the results of research data analysis, it showed an increase in student learning outcomes by using the fractional puzzle board media. This can be seen from the results of tests carried out by students in each cycle, in cycle I students get an average pre-test of 45% and post-test of 60%.In cycle II students get an average of pre-test of 75% and post-test 93.75%.